Lasiopodomys gregalis Pallas 1779 ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
101. Narrow-headed Vole Lasiopodomys gregalis French: Campagnol gréle / German: Schmalkopf-Wiihimaus / Spanish: Topillo de cabeza estrecha Other common names: Narrow-skulled Vole Taxonomy. Mus gregalis Pallas, 1779, E of Chulym River, Novosibirsk Region, Russia. Lasiopodomys gregalis is in subgenus Stenocranius. Morphologically and genetically, it is a sister species to L. raddei. In the past, it was placed in the genus Microtus. Within L. gregalis, there are three distinct mtDNA clades, north-western (northern, western, and central Siberia, Altai, and Tian Shan), central (Tuva), and south-eastern (south of eastern Siberia and northern Mongolia). The first clade is subdivided into six geographically distinct lineages: steppes of western Siberia, Yamal Peninsula and Northern Ural Mountains, northern Altai Mountains, southern Altai Mountains, Yakutia (= Sakha Republic), and Tian Shan. Phylogeographic structure reflects complex history of L. gregalis that includes a Middle Pleistocene dispersal from Altai ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 322, DOI: 10.5281/zenodo.6707142 ...